Assessment of Dietary Intake among Patients with Metabolic Syndrome and Comparison with Healthy Patients in Accordance with the Questionnaire - Ayaulym Nurgozhina (Journal of Global Pharma Technology, 2016)
Metabolic syndrome is a cluster of conditions that occur together, increasing the risk of heart disease, stroke, hypertension, and glucose intolerance. Metabolic syndrome has a major impact on the development of diabetes and cardiovascular diseases. Insulin resistance and β-cell function are also related to metabolic syndrome function. It is crucial to manage correct balance of energy requirement of cells and bodily inflammation for insulin sensitivity and control of metabolic syndrome [1].